Administration of epinephrine by advanced emergency medical technicians for out‐of‐hospital cardiac arrest in a rural emergency medical services system - Jared J. Bomba; Jamie Benson; David Hosmer; Daniel Wolfson (Journal of the American College of Emergency Physicians Open)
Abstract Objective Epinephrine in out‐of‐hospital cardiac arrest (OHCA) remains controversial and understudied in rural emergency medical services (EMS) systems. We evaluated the effects of allowing advanced emergency medical technicians (AEMTs) to administer epinephrine during OHCA in a rural EMS system. Methods An interrupted time series study was conducted using statewide EMS electronic records. Patients with OHCA before (phase I) and after (phase II) a protocol change expanding the AEMT scope of practice to include epinephrine for OHCA were identified. Number and timing of initial epinephrine administration, return of spontaneous circulation, and 30‐day survival rates were compared using descriptive statistics, logistic regression, regression discontinuity, and propensity score matching. Results A total of 1037 OHCAs met the inclusion criteria. In phase 1 compared with phase 2, 275 (56.12%) patients received epinephrine versus 624 (83.53%; P < 0.001). The mean time to first administration of epinephrine for unwitnessed and bystander‐witnessed OHCA were 11.73 minutes versus 8.17 minutes (P < 0.001) and 11.59 minutes versus 8.85 minutes (P < 0.01), respectively. Unadjusted analysis showed a decrease in 30‐day survival rates among patients receiving epinephrine from 18.01% to 12.66% (P < 0.05). Adjusted analysis showed an increase in 30‐day survival with decreased time to first epinephrine dose(OR 0.960, 1.005; 95% confidence interval, 0.929, 0.992). Conclusion Adding epinephrine for OHCA to the AEMT scope of practice was associated with an increased percentage of patients receiving epinephrine and decreased time to first administration of epinephrine for patients with unwitnessed OHCA. Unadjusted analysis showed a decrease in 30‐day survival rates among patients receiving epinephrine. Adjusted analysis found that earlier administrationof epinephrine was associated with increased ROSC and 30‐day survival.